Role of endogenous cortistatin in the regulation of ghrelin system expression at pancreatic level under normal and obese conditions. - Belén Chanclón (Public Library of Science (PLoS), 2013)
Ghrelin-system components [native ghrelin, In1-ghrelin, Ghrelin-O-acyltransferase enzyme (GOAT) and receptors (GHS-Rs)] are expressed in a wide variety of tissues, including the pancreas, where they exert different biological actions including regulation of neuroendocrine secretions, food intake and pancreatic function. The expression of ghrelin system is regulated by metabolic conditions (fasting/obesity) and is associated with the progression of obesity and insulin resistance. Cortistatin (CORT), a neuropeptide able to activate GHS-R, has emerged as an additional link in gut-brain interplay. Indeed, we recently reported that male CORT deficient mice (cort-/-) are insulin-resistant and present a clear dysregulation in the stomach ghrelin-system. The present work was focused at analyzing the expression pattern of ghrelin-system components at pancreas level in cort-/- mice and their control littermates (cort +/+) under low- or high-fat diet. Our data reveal that all the ghrelin-system components are expressed at the mouse pancreatic level, where, interestingly, In1-ghrelin was expressed at higher levels than native-ghrelin. Thus, GOAT mRNA levels were significantly lower in cort-/- mice compared with controls while native ghrelin, In1-ghrelin and GHS-R transcript levels remained unaltered under normal metabolic conditions. Moreover, under obese condition, a significant increase in pancreatic expression of native-ghrelin, In1-ghrelin and GHS-R was observed in obese cort+/+ but not in cort-/- mice. Interestingly, insulin expression and release was elevated in obese cort+/+, while these changes were not observed in obese cort-/- mice. Altogether, our results indicate that the ghrelin-system expression is clearly regulated in the pancreas of cort+/+ and cort -/- under normal and/or obesity conditions suggesting that this system may play relevant roles in the endocrine pancreas. Most importantly, our data demonstrate, for the first time, that endogenous CORT is essential for the obesity-induced changes in insulin expression/secretion observed in mice, suggesting that CORT is a key regulatory component of the pancreatic function.